2006
DOI: 10.1108/10222529200600003
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and fraud: any lessons for the auditor?

Abstract: The Prevention and Combating of Corrupt Activities Act, Act 12 of 2004, was instituted to curb corrupt activities. It imposes a duty on people in positions of authority to report corrupt or suspected corrupt activities and related activities. However, auditors are not listed in this Act as persons in a position of authority. This article discusses whether, despite the fact that the Prevention and Combating of Corrupt Activities Act does not place such a reporting duty on an auditor, auditors nevertheless have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…In the public sector auditing literature, there are studies relating auditing to corruption (Ahlenius, 2000;Atuilik, 2013;Blume & Voigt, 2011;Borge, 1999;Dipietro, 2011;Dye, 2007;Dye & Stapenhurst, 1998;Everett et al, 2007;Fan, 2012;Ferraz & Finan, 2008;Ferraz & Finan, 2011;Flint, 2005;Gherai et al, 2016;Gustavson & Sundström, 2016;Ionescu, 2014;Kassem & Higson, 2016;Kayrak, 2008;Khan, 2006;Labuschagne & Els, 2006;Liu & Lin, 2012;Melo, Pereira, & Figueiredo, 2009;Morehead, 2007;Neu, Everett, & Rahaman, 2013a;Neu, Everett, & Rahaman, 2015;Neu, Everett, Rahaman, & Martinez, 2013b;Olken, 2007;Otalor & Eiya, 2013;Othman, Aris, Mardziyah, Zainan, & Amin, 2015;Suzuki, 2004;Tara et al, 2016;Tunley, Button, Shepherd, & Blackbourn, 2017;Vanasco, 1998). Several ISSN 1946-052X 2018 studies have investigated empirically the importance of public sector auditing in fighting corruption.…”
Section: Discussionmentioning
confidence: 99%
“…In the public sector auditing literature, there are studies relating auditing to corruption (Ahlenius, 2000;Atuilik, 2013;Blume & Voigt, 2011;Borge, 1999;Dipietro, 2011;Dye, 2007;Dye & Stapenhurst, 1998;Everett et al, 2007;Fan, 2012;Ferraz & Finan, 2008;Ferraz & Finan, 2011;Flint, 2005;Gherai et al, 2016;Gustavson & Sundström, 2016;Ionescu, 2014;Kassem & Higson, 2016;Kayrak, 2008;Khan, 2006;Labuschagne & Els, 2006;Liu & Lin, 2012;Melo, Pereira, & Figueiredo, 2009;Morehead, 2007;Neu, Everett, & Rahaman, 2013a;Neu, Everett, & Rahaman, 2015;Neu, Everett, Rahaman, & Martinez, 2013b;Olken, 2007;Otalor & Eiya, 2013;Othman, Aris, Mardziyah, Zainan, & Amin, 2015;Suzuki, 2004;Tara et al, 2016;Tunley, Button, Shepherd, & Blackbourn, 2017;Vanasco, 1998). Several ISSN 1946-052X 2018 studies have investigated empirically the importance of public sector auditing in fighting corruption.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because some authors consider fraud and corruption to be two different offenses (e.g. Labuschagne and Els, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Auditing can help to curb corruption because auditors can take appropriate action if they find facts which give them areason to believe that a corrupt activity amounting to an irregularity has been committed. The possible effects of the corrupt activity will also be documentedin the audit report (Labuschagne & Els, 2006). Unfortunately, Bussell (2010) found that policy initiatives intended to reduce corruption are least likely to be implemented in countries that have high levels of corruption.…”
Section: Strategies To Curb Corruption and Improve Service Deliverymentioning
confidence: 99%